An exploration of flavours in studies of e‐cigarettes for smoking cessation: secondary analyses of a systematic review with meta‐analyses. (5th December 2022) - Lindson, Nicola; Butler, Ailsa R.; Liber, Alex; Levy, David T.; Barnett, Phoebe; Theodoulou, Annika; Notley, Caitlin; Rigotti, Nancy A.; Hartmann‐Boyce, Jamie
Abstract: Aims: To estimate associations between e‐cigarette flavour and smoking cessation and study product use at 6 months or longer. Methods: Secondary analysis of data from a living systematic review, with meta‐analyses and narrative synthesis, incorporating data up to January 2022. Included studies provided people who smoked combustible cigarettes with nicotine e‐cigarettes for the purpose of smoking cessation compared with no treatment or other stop smoking interventions. Measurements included smoking cessation and study product use at 6 months or longer reported as risk ratios (RR) with 95% confidence intervals (CI); and flavour use at any time‐points. Results: We included 16 studies ( n = 10 336); 14 contributed to subgroup analyses and 10 provided participants with a choice of e‐cigarette flavour. We judged nine, five and two studies at high, low and unclear risk of bias, respectively. Subgroup analyses showed no clear associations between flavour and cessation or product use. In all but one analysis, tests for subgroup differences resulted in I 2 values between 0 and 35%. In the comparison between nicotine e‐cigarettes and nicotine replacement therapy (NRT) ( I 2 = 65.2% for subgroup differences), studies offering tobacco flavour e‐cigarettes showed evidence of a greater proportion of participants still using at 6 months or longer (RR = 3.81; 95% CI = 1.45–10.05; n = 1181; I 2 = 84%), whereas there was little evidence for greater 6‐month use when studies offered a choice of flavours (RR = 1.44; 95% CI = 0.80–2.56; n = 454; I 2 = 82%). However, substantial statistical heterogeneity within subgroups makes interpretation of this result unclear. In the 10 studies where participants had a choice of flavours, and this was tracked over time, some switching between flavours occurred, but there were no clear patterns in flavour preferences. Conclusions: There does not appear to be a clear association between e‐cigarette flavours and smoking cessation or longer‐term e‐cigarette use, possibly due to a paucity of data. There is evidence that people using e‐cigarettes to quit smoking switch between e‐cigarette flavours.